1980
DOI: 10.1016/0021-9797(80)90308-2
|View full text |Cite
|
Sign up to set email alerts
|

The zno/aqueous solution interface. I. Capacity of the double layer

Abstract: At the ZnO/aqueous electrolyte solution interface, three processes occur on changing the pH of the medium: (a) adsorption of H ÷ or OH-; (b) dissolution or precipitation of ZnO; (c) a slow process consuming H + or OH-, A technique is described by which these processes can be separated. When due allowance is made for the slow process and when the influence of changes in solubility is eliminated, the capacity due to adsorption of H ÷ or OH-alone can be calculated: it is significantly smaller than that found by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…show the same characteristics as reported by Trimbos et al (5), which had been found by other investigators as well (2, 3). Thus, a fast H ÷ or OH-consumption was followed by a slow process.…”
Section: Measurements Of Foh-_h+supporting
confidence: 91%
See 3 more Smart Citations
“…show the same characteristics as reported by Trimbos et al (5), which had been found by other investigators as well (2, 3). Thus, a fast H ÷ or OH-consumption was followed by a slow process.…”
Section: Measurements Of Foh-_h+supporting
confidence: 91%
“…Thus, we must conclude that this slow process is connected with surface carbonate groups rather than with a surface reaction involving ZnOH groups with mobile charge cartiers, as suggested earlier by the kinetics of the process (5). Similarly slow H + or OH-consumption as found for ZnO a.r.…”
Section: Measurements Of Foh-_h+mentioning
confidence: 52%
See 2 more Smart Citations
“…The semiconductor/electrolyte solution interface system (16-18) was studied in order to explain the phenomenon of electron transfer between semiconductor and electrolyte (16,17,20). The semiconductor/electrolyte solution interface has been studied by comparing the P-N junction (18)(19) because of the phenomenological similarities found between semiconductor/electrolyte and P-N junctions (16,19,20,23).…”
Section: Theoretical Aspectsmentioning
confidence: 99%